2018
DOI: 10.2478/ajis-2018-0050
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Traditional Weaning practices in North Western Nigeria; Food, Knowledge and Culture: A Step towards Safeguarding Community Food Security

Abstract: For many women in Nigeria who practice exclusive breast feeding, the weaning period is a crucial time. This is when children are introduced to solid food and such dietary change can be challenging for them, but also for care givers who are saddled with the responsibility of providing sufficient and nutritious food that would support healthy development. At this period, many women in rural communities utilize traditional foods of various kinds as weaning food. This paper highlights traditional food used by care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Based on the joint recommendation of the WHO and the United Nations Children’s Fund (UNICEF), the introduction of nutritionally-adequate and safe complementary foods to an infant should be at 6 months 7 . However, results from this study showed that most infants were introduced to complementary feeding (62.5%) as early as 3–5 months old and water (43.3%) at 3 months old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the joint recommendation of the WHO and the United Nations Children’s Fund (UNICEF), the introduction of nutritionally-adequate and safe complementary foods to an infant should be at 6 months 7 . However, results from this study showed that most infants were introduced to complementary feeding (62.5%) as early as 3–5 months old and water (43.3%) at 3 months old.…”
Section: Discussionmentioning
confidence: 99%
“…The food given to children during their weaning period is very crucial as an inadequate complementary diet will significantly inhibit the child's optimum growth, health and cognitive development in the future 7 , 8 . Consequently, a complementary food should be healthy, adequate and should start timely.…”
Section: Introductionmentioning
confidence: 99%
“…Positive traditional practices: e.g., including groundnuts in infant diets and using fermentation to reduce contamination in Nigeria ( 41 )…”
Section: Resultsmentioning
confidence: 99%
“…These primarily descriptive norms that everyone feeds infants easily chewed and digested foods shaped practices such as avoiding or delaying animal-source and other nutritious foods ( 30 – 34 ) or, in Laos, premasticating meat and other foods before feeding to the child ( 36 ). Willingness to adopt new behaviors that increase dietary diversity can be constrained by social norms related to fear of being perceived as not providing appropriate care or food to children, because certain foods were thought to promote or interfere with physical development and well-being ( 32 , 33 , 39 , 41 43 ). Beliefs about how foods affect child psychosocial development and behavior were also reported.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies recommend considering information sharing, role modeling, and environment to address associated practices hindering breastfeeding and weaning practices (Nandagire et al, 2019 ). This concept analysis also provides a basis to establish patterns of the weaning process not just by food preferences and restrictions (Oloko & Ekpo, 2018 ), but it can be the basis of exploring the weaning process considering maternal-infant attachment or emotional readiness of the mother and the baby.…”
Section: Discussionmentioning
confidence: 99%